Evaluation of thermodynamics properties of ethanol-water mixtures (I) - Osney Pérez Ones; Jorge Díaz Rodríguez; Lourdes Zumalacárregui; Osvaldo Gozá León (Revista Facultad de Ingeniería Universidad de Antioquia, 2013)
In this work, models and algorithms to estimate thermodynamics properties in ethanol-water mixtures are shown for different pressures. This is achieved through a quick and simple method, requiring minimum information, of measurable properties. Models to estimate enthalpy, heat capacity, latent heat, entropy and activity coefficients models are based on thermodynamics principles and statistic methods. Specific enthalpies values obtained are compared with different literature sources, showing satisfactory adjustments.